Analysis Of Principal Decision Making Policies Using Comprehensive Rational Models At SDS Santa Lusia Sei Rotan - Ester Justina Sinaga; Saloma Banjarnahor; Saut Purba; Irsan Rangkuti; Nasrun Nasrun (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to analyzePrincipal Decision Making Policy using the Comprehensive Rationale Model at SDS Santa Lucia Sei Rotan. The type of research used in this research is descriptive research with a quantitative approach. The subjects in this study were 15 class teachers, while the object of this study was the principal's decision-making policy using a comprehensive rational model. The results obtained from the 20 question items were 15 statements that received very good categories, 3 items in the good category, 1 item in the sufficient category, 1 item in the very poor category and described the total acquisition score of 20 question items with an overall acquisition score of 279 percentage 93% and categorized as very good. The acquisition of this score indicates that the implementation of decision-making policies using a comprehensive rational model has been carried out by the school principal very well.